Rancang Bangun Alat Pendeteksi Kebocoran Gas LPG Berbasis Internet of Things Dengan Katup Regulator Otomatis - Venna Valencia; Louis Putra Purnama; Chandra Tjong; Johansah Liman (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2022)
Liquefied Petroleum Gas (LPG) is a flammable gas. Leaks in LPG gas cylinders that are not known to the user can have a fatal impact if there is no system that detects and stop the leak. Therefore, this study designed a system to detect and solve LPG gas leaks based on the Internet of Things automatically. The way this system works is that the MQ-6 sensor detects the concentration of LPG gas around the cylinder with an analog value limit when the safe condition is <400 and the danger condition is 400. The sensor will continue to detect as long as the tool is on and send data to the microcontroller in the form of NodeMCU ESP8266 which then transmits the data to Firebase. From Firebase, users will get information about LPG gas levels in safe/dangerous conditions, gas position control, as well as fan and buzzer conditions through a smartphone application in real time. If the conditions are safe, the green LED will light up and the condition is dangerous, the microcontroller will physically respond to the servo motor to turn the regulator valve open, the fan, the red LED and the buzzer while virtually the user will get information through the application and notifications via the WhatsApp application in the form of a short message as a warning that gas was detected. The test results show that the LPG gas detection system can work well.